Effect of cadre-based empowerment on antenatal care knowledge, attitudes, and antenatal care visit among pregnant women - Yuniarti, Yuniarti; Yorita, Epti; Widiyanti, Desi; Destariyani, Elvi (Jurnal Kesehatan Ibu dan Anak, 2024)
Despite ongoing efforts to reduce maternal mortality in Indonesia, antenatal care (ANC) coverage—particularly completion of ?4 visits (K4)—remains suboptimal in regions such as Bengkulu City. The involvement of community health cadres is recognized as a key strategy to improve maternal health outcomes; however, limited research has directly examined the effect of structured cadre-based empowerment on ANC knowledge, attitudes, and service utilization. This study aimed to examine the effect of ANC cadre empowerment on ANC knowledge, attitudes, and the frequency of ANC visits among pregnant women in Bengkulu City, Indonesia.This quasi-experimental study employed a pre-test and post-test control group design involving 40 pregnant women in Bengkulu City, Indonesia divided equally into intervention and control groups. The intervention group received structured cadre-based empowerment involving trained health cadres, while the control group received standard counseling. Data were analyzed using Wilcoxon and Mann-Whitney tests to assess differences in knowledge, attitudes, and ANC visit frequency. After the intervention, the knowledge scores in the intervention group significantly increased from 53.80 to 73.90 (p=0.020), while the control group showed no significant change. Attitude scores in the intervention group also increased significantly from 35.35 to 38.25 (p=0.014), unlike the control group (p=0.320). Regarding ANC visits, the intervention group had a higher mean number of visits (mean=4) compared to the control group (mean=3), with a statistically significant difference (p=0.001). Cadre-based empowerment through structured training significantly improved pregnant women’s knowledge, attitudes, and ANC service utilization. This suggests the importance of integrating cadre empowerment models into routine maternal health programs to support improved ANC compliance.